2023
DOI: 10.1029/2022gb007678
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Changes in Concentration and Yield of Riverine Dissolved Silicon From the Poles to the Tropics

Kathi Jo Jankowski,
Keira Johnson,
Lienne Sethna
et al.

Abstract: Riverine exports of silicon (Si) influence global carbon cycling through the growth of marine diatoms, which account for ∼25% of global primary production. Climate change will likely alter river Si exports in biome‐specific ways due to interacting shifts in chemical weathering rates, hydrologic connectivity, and metabolic processes in aquatic and terrestrial systems. Nonetheless, factors driving long‐term changes in Si exports remain unexplored at local, regional, and global scales. We evaluated how concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 116 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…In addition, the weathering of this biogenic silica in the hyporheic zone may contribute to dissolved silicon in the streamwater, as indicated by the analysis of silicon isotopes by Hirst et al (2020) and Hatton et al (2020) . Taken as a whole, these findings suggest that silicon transport in these streams may be influenced by autochthonous biological processes in the stream and its hyporheic zone to a much greater extent than in streams and rivers in other regions where allochthonous watershed biogeochemical processes are dominant ( Jankowski et al, 2023 ).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the weathering of this biogenic silica in the hyporheic zone may contribute to dissolved silicon in the streamwater, as indicated by the analysis of silicon isotopes by Hirst et al (2020) and Hatton et al (2020) . Taken as a whole, these findings suggest that silicon transport in these streams may be influenced by autochthonous biological processes in the stream and its hyporheic zone to a much greater extent than in streams and rivers in other regions where allochthonous watershed biogeochemical processes are dominant ( Jankowski et al, 2023 ).…”
Section: Discussionmentioning
confidence: 91%
“…Continued, or enhanced Si loading from Yedoma deposit erosion may further enhance the potential for Si burial and recycling in the Arctic Ocean. Changing riverine inputs, considering total discharge, total Si load, and the balance of DSi and ASi (Carey et al, 2020;Frey et al, 2007;Jankowski et al, 2023;Tank et al, 2023) will likely play an important role in regulating future rates of Si burial and recycling on Arctic continental shelves. Beyond the Arctic Ocean, exported Si from the Arctic Ocean fuels one of the most productive regions in the world, the North Atlantic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Arctic Ocean is changing rapidly, particularly in the shallow shelf areas due to climate change with warmer waters, less ice, increased primary production, and accelerating coastal erosion (Gustafsson et al., 2011; Lewis et al., 2020; Meredith et al., 2019; Terhaar et al., 2020; Wild et al., 2019). Further, riverine inputs of Si to the Arctic Ocean may also be changing (Jankowski et al., 2023; Tank et al., 2023). As continental shelf areas make up more than half of the area of the Arctic Ocean (∼53% of the Arctic Ocean; Jakobsson, 2002), understanding the Si cycle in these regions is necessary to project how the Arctic Ocean Si budget might respond to changing ocean and climate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in Si concentrations with respect to other nutrients (i.e., nitrogen and phosphorus) may facilitate preferential growth of potentially harmful, non-silicious algae, with effects on water quality and ecosystem health (Conley et al 1993;Turner et al 2003). A recent synthesis of long-term trends in fluvial Si concentrations and loads from 60 streams showed that Si concentrations were changing, and that the timing of change during the year varied across and within biomes (Jankowski et al 2023), indicating widespread changes in Si watershed processing may be occuring.…”
Section: Introductionmentioning
confidence: 99%